The Role and Mechanism of Pyroptosis and Potential Therapeutic Targets in Sepsis: A Review - Zheng, Xiangtao; Chen, Weiwei; Gong, Fangchen; Chen, Ying; Chen, Erzhen (Frontiers in Immunology, 2021)
Sepsis is defined as life-threatening organ dysfunction caused by a dysregulated host response to infection. Recently it has been found that pyroptosis is a kind of proinflammatory programmed death, which is different from apoptosis. More and more studies have been focused on pyroptosis and its relationship with sepsis, mainly including the new mechanisms, role, relevant targets of pyroptosis in sepsis. Obviously, moderate pyroptosis in sepsis can control pathogen infection; However, excessive activation of pyroptosis can lead to a dysregulated host immune response and even organ dysfunction. This review provides an overview of the mechanisms and potential therapeutic targets underlying pyroptosis in sepsis during recent decades, looking forward to the future direction of treatment for sepsis.